2019
DOI: 10.1103/physrevb.99.140502
|View full text |Cite
|
Sign up to set email alerts
|

Mass transport through dislocation network in solid He4

Abstract: We studied the transport of 4 He atoms through 2.5 mm thick solid 4 He samples sandwiched between two superfluid leads with five different tailored made sample cells. Measurements in a cell with a barrier at the center of the solid samples and in a cell filled with silica aerogel establish the causal relation between the observed mass flow and the dislocation network in the solid sample. Comparing the results from these cells and prior measurements on solid samples with thicknesses of 2 cm and 8 µm reveals tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 28 publications
3
19
0
Order By: Relevance
“…Networks of metallic domain walls have previously been observed in Cu-intercalated TiSe 2 41 , and also in other contexts: integer quantum Hall systems 42 , magnetically ordered systems 43 , nearly commensurate charge density wave systems 44 , and also recently in moiré systems [45][46][47][48] with periodic networks determined by the moiré pattern. Remarkably, power laws have also been observed in the mass transport through a network of dislocations in solid 4 He generated by a pressure difference 49 , suggesting a more ubiquitous occurrence of the network of narrow channel transport. The mechanism for the generation of networks is system-specific-disorder, quench, dislocation, etc.…”
Section: Emergent Network Of Narrow Transport Channelsmentioning
confidence: 95%
“…Networks of metallic domain walls have previously been observed in Cu-intercalated TiSe 2 41 , and also in other contexts: integer quantum Hall systems 42 , magnetically ordered systems 43 , nearly commensurate charge density wave systems 44 , and also recently in moiré systems [45][46][47][48] with periodic networks determined by the moiré pattern. Remarkably, power laws have also been observed in the mass transport through a network of dislocations in solid 4 He generated by a pressure difference 49 , suggesting a more ubiquitous occurrence of the network of narrow channel transport. The mechanism for the generation of networks is system-specific-disorder, quench, dislocation, etc.…”
Section: Emergent Network Of Narrow Transport Channelsmentioning
confidence: 95%
“…Many features of the UMass experiment have been confirmed by us in two separate experiments on solid samples of 8 µm and 2.5 mm in thickness [6,7]. Our study on 2.5 mm thick solid samples, carried out in 5 sample cells of different designs verifies the proposal of UMass's group by establishing a direct causal relation between mass flow and dislocation network in the solid; specifically we show mass flow takes place through, instead of around the solid sample contrary to that suggested by an experiment at the University of Alberta [8] and that no mass flow can be found in solid samples grown inside silica aerogel missing a dislocation network.…”
mentioning
confidence: 53%
“…However, in the latter experiment the mass flow extinction was absent. In the work [135] with solid samples of about 2 mm thickness, a typical flux of approximately 2.5 × 10 −8 g/mm 2 s is found. In general, it has been shown that thinner samples result in higher values of the flux, with the mass flow rate decreasing logarithmically with the thickness of the solid 4 He.…”
Section: Mass Flux Experimentsmentioning
confidence: 85%